Galvanic electrochemical cells: a study of the understanding and knowledge responses genera ted by students tested as individuals, in pairs and in groups - Gallant, Moegamad Riedwaan (School of Education, 2019)
This investigation is an application and extension of the work of Swain (1999) who recorded the productivity of the responses generated by student groups of different sizes during science lessons. The present study selected the topic Galvanic Electrochemical Cells. It sought to gather achievement data from 584 high school students studying physical science by recording their technical knowledge responses generated under several different socially-determined conditions. The investigation proceeded in three phases: - xi In phase 1, physical science students in Western Cape high schools were taught the textbook chapter Galvanic Electrochemical Cells by their usual chemistry teachers in normal classroom lessons, without any special programme of external assistance. At the same time, the researcher was formulating, designing, compiling, trialing and defining a summative set of twelve achievement test questions covering the topics oxidation, reduction, electrode current flow, forms of energy, salt bridge, oxidation and reduction half reactions and industrial applications of electrochemical cells. The wording and content of the final full electrochemistry test was progressively improved through three pilot trials involving consecutive groups of 63, 34 and 79 students; after which it became a self-evaluation worksheet scoring 30 marks. This worksheet test was then utilized for both formative and summative purposes, in two further phases.